2009
DOI: 10.1093/geronb/gbp096
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Values and Caregiving: The Updated Sociocultural Stress and Coping Model

Abstract: This review revises the sociocultural stress and coping model for culturally diverse family caregivers proposed in 1997 by Aranda and Knight. Available research on the influence of cultural values on the stress and coping process among family caregivers supports a common core model that is consistent across ethnic groups and that links care recipients' behavior problems and functional impairments to caregivers' burden appraisals and health outcomes. Familism as a cultural value appears to be multidimensional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
325
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(372 citation statements)
references
References 32 publications
26
325
1
2
Order By: Relevance
“…Family Caregivers as the basis for analysis for all four focus groups' qualitative data [18]. We found some significant differences in the cultural values and norms that shaped the caregiving experience.…”
Section: Qualitative Results We Used the Updated Sociocultural Stresmentioning
confidence: 91%
See 2 more Smart Citations
“…Family Caregivers as the basis for analysis for all four focus groups' qualitative data [18]. We found some significant differences in the cultural values and norms that shaped the caregiving experience.…”
Section: Qualitative Results We Used the Updated Sociocultural Stresmentioning
confidence: 91%
“…We utilized The Updated Sociocultural Stress and Coping Model to guide our data analysis [18]. Two researchers from the team analyzed the focus group transcripts using the following steps.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the broader focus of this study design did not allow in-depth explorations of other important aspects of family caregiving and associated burden, such as impact on caregiver quality of life, physical health, or stress-buffering supports, which have been the focus of other studies. 11,12,15,40 Finally, the WMH surveys did not collect data on the number of family members a respondent had and/or lived with, the extent of relatives that were encompassed within the core family in different countries, or the number of family members of a given type with a particular type of illness, imposing restrictions on the extent to which we could carry out finegrained analyses of complex caregiving situations.…”
Section: Discussionmentioning
confidence: 99%
“…Filial piety is another cultural value identified in the literature, although it has received limited attention; it has been defined as familial respect and the prioritization of the family's needs over the individual's needs (McCleary & Blain, 2013). Research conducted by Chun (as cited in Knight et al, 2010) revealed that this particular cultural value may be associated with adaptive coping styles, such as problem-focused coping. Thus, research exploring familism and filial piety has supported a relationship between cultural values and coping.…”
Section: Cultural Values and Motivations In Caregiversmentioning
confidence: 99%